Guggenheim International Exhibition 1967 : Sculpture from twenty nations. - Art Gallery of Ontario, Toronto; The National Gallery of Canada, Ottawa; Montreal Museum of Fine Arts, Montreal (New York : The Solomon R. Guggenheim Museum, 1967)
Arp, Jean ; Kiesler, Frederick ; Giacometti, Alberto ; Diller, Burgoyne ; Smith, David ; Kemeny, Zoltan ; Picasso, Pablo ; Lipchtiz ; Calder ; Moore ; Colla ; Fontana ; Nevelson ; Marini ; Hepworth ; Noguchi ; Rickey ; Wotruba ; Bill ; Manzu ; etc.
Guggenheim International Exhibition 1967 : Sculpture from twenty nations, The Solomon R. Guggenheim Museum, New York, October 20, 1967 - February 4, 1968 ; Art Gallery of Ontario, Toronto, February - March 1968 ; The National Gallery of Canada, Ottawa, April - May 1968 ; Montreal Museum of Fine Arts, Montreal, June - August 1968
boek